Sex differences in feeding behavior in rats: the relationship with neuronal activation in the hypothalamus - Fukushima, Atsushi; Hagiwara, Hiroko; Fujioka, Hitomi; Kimura, Fukuko; Akema, Tatsuo; Funabashi, Toshiya (Frontiers in Neuroscience, 2015)
There is general agreement that the central nervous system in rodents differs between sexes due to the presence of gonadal steroid hormone during differentiation. Sex differences in feeding seem to occur among species, and responses to fasting (i.e., starvation), gonadal steroids (i.e., testosterone and estradiol), and diet (i.e., western-style diet) vary significantly between sexes. The hypothalamus is the center for controlling feeding behavior. We examined the activation of feeding-related peptides in neurons in the hypothalamus. Phosphorylation of cyclic AMP response element-binding protein (CREB) is a good marker for neural activation, as is the Fos antigen. Therefore, we predicted that sex differences in the activity of melanin-concentrating hormone (MCH) neurons would be associated with feeding behavior. We determined the response of MCH neurons to glucose in the lateral hypothalamic area (LHA) and our results suggested MCH neurons play an important role in sex differences in feeding behavior. In addition, fasting increased the number of orexin neurons harboring phosphorylated CREB in female rats (regardless of the estrous day), but not male rats. Glucose injection decreased the number of these neurons with phosphorylated CREB in fasted female rats. Finally, under normal spontaneous food intake, MCH neurons, but not orexin neurons, expressed phosphorylated CREB. These sex differences in response to fasting and glucose, as well as under normal conditions, suggest a vulnerability to metabolic challenges in females.